Effect of filling materials on reclaimed soil potassium adsorption and desorption in mining area - Kexin JING; Zhoubin DONG; Huaizhi BO; Zhiliang WANG; Shaohao HU; Xinju LI; Xiangyu MIN (Meitan xuebao)
Coal mining causes land subsidence, soil degradation, and nutrient depletion in agricultural areas. Filling and reclamation with various materials is a common method for restoring subsided land in the eastern mining areas of China. It is essential to explore potassium availability in reclaimed minesoils, as Potassium is a critical element for crop growth and development. To investigate the potassium availability of reclaimed minesoils and their influencing factors, we select the reclaimed minesoils filled with coal gangue (MGS), lake mud (HN), and Yellow River sand (HHS) as the research samples. X-ray diffraction (XRD), Fourier transform infrared spectrometer (FTIR), scanning electron microscope (SEM), and specific surface and porosity analyzer (BET) are used to characterize the reclaimed soil. And determine the adsorption and desorption kinetics of the reclaimed soil through adsorption isotherm experiments and continuous-flow liquid method, and describe using the corresponding models. The results showed that the mineral composition, functional group composition, microscopic morphology, and surface structure of reclaimed minesoils filled with various materials differed from normal cultivated soil (ZC). The XRD patterns and FTIR curves of the reclaimed minesoils showed weakened diffraction peaks of illite and characteristic peaks of —OH groups caused by illite. Additionally, the surface of the reclaimed mine soils appeared smoother, and the specific surface area and pore volume were smaller than ZC. The adsorption-desorption parameters of reclaimed minesoils are lower than those of ZC. The MGS exhibits the largest adsorption capacity, with a maximum adsorption capacity (Qm) of 7.90−15.00 mg/g, while the HHS exhibits the lowest adsorption capacity, with a Qm of only 2.66−3.91 mg/g. The differences in desorption capacities of reclaimed minesoils are insignificant, as they all remain relatively low. The equilibrium desorption capacity (Qe4) of the reclaimed minesoils filling layer filled with coal gangue (MGST) is the largest, reaching 4.40 mg/g. The Qe4 of the reclaimed minesoils backfilling layer filled with Yellow River sand (HHST) is the lowest, only 1.81 mg/g. The adsorption parameters, including maximum adsorption capacity and equilibrium adsorption capacity, of the reclaimed minesoils showed significant correlations with water content, soil texture (silt, sand), cation exchange, and surface characteristics (specific surface area, pore volume, and average pore size). The desorption parameter (equilibrium desorption) exhibited significant correlations with water content, clay content, and cation exchange. Studies show that filling typical materials will reduce the potassium availability in reclaimed minesoils, which is mainly related to the adsorption and desorption capacity of reclaimed minesoils potassium. MGS and HN exhibit greater adsorption capacity due to their larger specific surface area, clay content, and cation exchange capacity. However, they are mainly irreversible adsorption due to their high illite and —OH content, which can be mitigated by grinding and sieving the filling materials to reduce particle size and adjusting the pH appropriately; HHS has a lower adsorption and desorption capacity due to its small specific surface area, clay content, and cation exchange capacity, which can be improved by adding clay to reclamation and using —OH-rich materials such as straw to calcine and prepare HHS materials suitable for filling and reclamation.